Playing together: towards a theory of the British sports club in history. Issue 3 (15th March 2016) - Vamplew, Wray
Abstract: This article brings together theories and extant analysis to assist in a better understanding of the theoretical complexities of establishing, organising, operating, and sustaining the sports club. It explores theoretical perspectives on the origins of the club; various levels of associativity; capital formation particularly that involving social capital; conviviality; the life cycle of the club; and aspects of third sector theory, the economics of the firm and invention and innovation.